Analysis of Legal Actions for Civil Claims of First Travel Fraud Victims Post Jurisdiction of the Supreme Court Number 3096k/Pid.Sus/2018 in Demanding Damages - Ni Nyoman Intan Pratiwi Rahmawati; Tunggul Anshari Setia Negara; Hendarto Hadisuryo (Budapest International Research and Critics University, 2022)
This article is entitled